2019
DOI: 10.1111/sapm.12279
|View full text |Cite
|
Sign up to set email alerts
|

Finite‐size corrections at the hard edge for the Laguerre β ensemble

Abstract: A fundamental question in random matrix theory is to quantify the optimal rate of convergence to universal laws. We take up this problem for the Laguerre β ensemble, characterized by the Dyson parameter β, and the Laguerre weight xae−βx/2, x>0 in the hard edge limit. The latter relates to the eigenvalues in the vicinity of the origin in the scaled variable x↦x/4N. Previous work has established the corresponding functional form of various statistical quantities—for example, the distribution of the smallest eige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
(166 reference statements)
1
17
0
Order By: Relevance
“…12 & 13], which are well suited to the analysis of the rate of convergence to the hard edge limit. This circumstance similarly holds true for the Laguerre case of (A.1), for which an analysis of the rate of convergence has recently been carried out in [23].…”
Section: Appendix Amentioning
confidence: 56%
See 1 more Smart Citation
“…12 & 13], which are well suited to the analysis of the rate of convergence to the hard edge limit. This circumstance similarly holds true for the Laguerre case of (A.1), for which an analysis of the rate of convergence has recently been carried out in [23].…”
Section: Appendix Amentioning
confidence: 56%
“…Recalling (1.6), we see from (3.10) that in general for products of Laguerre unitary ensembles, the pointwise rate of convergence to the hard edge limiting k-point correlation is O(1/N ). On the other hand, as noted in the text around (1.11), earlier works [8,11,23,27,43] have demonstrated that for the Laguerre unitary ensemble itself (the case M = 1), with the hard edge scaling variables as used in (3.10), and with the Laguerre parameter a = 0, the convergence rate is actually O(1/N 2 ). Moreover, these same references found that the O(1/N 2 ) rate holds for general Laguerre parameter a > −1 if each N on the LHS of (3.10) is replaced by N + a/2.…”
Section: 1mentioning
confidence: 91%
“…Remark 2.4. The analytic structure of an exponential times a polynomial has been present, and played an important role, in a number of recent studies of distributions in random matrix theory [36,22,27].…”
Section: Generalising (115)mentioning
confidence: 99%
“…A recent application of the differential-difference system to the computation of some structured formulas for the distribution of the smallest and largest eigenvalues of the β-Jacobi ensemble, applicable in certain parameter ranges, has been given in [14]. In the case of the β-Laguerre ensemble analogue of (2.17), the works [24,13,17] exhibit analogous applications. For present purposes, a particular change of variables and limit of (2.17) and (2.18) is required.…”
Section: The Differential-difference System Let C Nmentioning
confidence: 99%